Glass forming ability of materials: A thermodynamic approach - Mishra R.K.; Dubey K.S. (My University, 2025)
The glass forming ability of materials has been studied on the basis of the critical cooling rate (Rc) for the glass formation. The study is made by obtaining an analytical expression for the nose temperature (Tn) of the time-temperature-transformation (T-T-T) diagram using the expressions for the thermodynamic quantities Gibbs free energy difference (ΔG), entropy difference (ΔS) and enthalpy difference (ΔH) between the undercooled liquid and solid phases obtained on the basis of Taylor's series expansion. The study is made for oxide as well as for polymeric glasses by calculating Rc for SiO2, B2O3, O-terphenyl, 2-methylpentane, glycerol and ethanol. The variations of Rc with the reduced ideal glass transition temperature (TK/Tm) as well as with the ratio of specific heat and entropy differences (Δ Cpm / Δ Sm) at the melting temperature (Tm) have been analyzed, where TK is the ideal glass transition temperature. It is found that material having a large value of the reduced ideal glass transition temperature (TK/Tm) results a lower value of Rc. It is also found that Rc decreases with increasing Δ Cpm / Δ Sm. Attempt has also been made to study the glass forming ability of materials on the basis of reduced residual entropy (Δ SR / Δ Sm) and (Tg - TK) / Tm, where Tg is the glass transition temperature and it is found that the material having a lower reduced residual entropy (Δ SR / Δ Sm) requires a lower Rc to convert into a glassy structure. It is also found that the materials having low (Tg - TK) / Tm require low Rc and consequently such materials can be said as a good glass former. © 2009 Elsevier B.V. All rights reserved.